GPSR ALGORITHM TO OVERCOME THE LIMITATION IN PUBLIC KEY INFRASTRUCTURE FOR SECURITY IN SMART GRID COMMUNICATION - Nita Jadhav; Nita Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
Smart grid communication is the generic label for the application of the computer intelligence and networking abilities. Smart grid adds new functionalities to electrical power systems. Because of this, many security problems arises. For security in small grid communication, many types of protocols and infrastructures use their own set of security requirements. Public key infrastructure is one of the solutions for ensuring security in the smart grid communication. Although PKI is viable solution, it has some difficulties to satisfy the requirements in availability, privacy preservation and scalability. The wireless mesh network technology is the promising infrastructure solution tosupport smart functionality, scalability, as well as it can provide redundant routes for the smart grid communication network to guarantee the network availability. Greedy perimeter stateless routing algorithm is useful in wireless mesh network technologyto overcome the limitations that occurs in the public key infrastructure for the security in smart grid communication